Teachers’ Well-Being During the COVID-19 Pandemic in Northern Palawan - Jarabejo-Gaviana, Rowena (Journal of Interdisciplinary Perspectives, 2025)
The study’s main objective is to investigate teachers’ experiences affecting their well-being during the COVID-19 pandemic in Northern Palawan, focusing on their psychological, emotional, social, and economic experiences. Employing a phenomenological qualitative approach, in-depth interviews were conducted with nine (9) purposively qualified teachers who participated in the guided interviews to capture the educators' lived experiences and understand teachers’ perspectives amidst the health crisis. The study reveals impacts on educators’ mental health, instructional efficacy, and systemic inequalities. Seven (7) significant challenges were pointed out namely: 1) health anxiety- dominated teachers’ experiences, with fear of infection exacerbating stress, absenteeism, and burnout 2) module preparation- became a crisis due to delayed MOOE funds forcing teachers to self-funding printing, worsening workloads, and leaving 67% of students without 1:1 materials until quarter four, 3) struggling learners regressed academically, with 67% of teachers reporting Grade two pupils unable to read and write, compounded by parental support, 4) ICT challenges- older and rural educators struggling with zoom and online tools, widening the digital divide, 5) co-teachers conflicts- less frequent (33%) strained collaboration and required administrative mediation, 6) heavy workloads- this study pointed out that overloading tasks topped the challenges encountered by teachers followed by family-related concerns, 7) financial issues. On the other hand, building a strong relationship with peers and immediate family members became an enabling strategy in dealing with the enumerated challenges. The results reveal significant emotional and psychological stressors linked to family concerns, health risks, and work demands. However, teachers demonstrated notable resilience, bolstered by personal faith, family support, and collegial relationships. Coping strategies included a sense of purpose, maintaining social connections, and dedication to their students. The findings underscore the critical role of emotional support and adaptive strategy in fostering teacher resilience, with implications for future support programs. This study emphasizes the urgent need to prioritize teacher well-being and systemic preparedness to build a crisis-resilient education system.